Estado nutricional y rendimiento académico en los estudiantes de la escuela “Dr. Edison Calle Loaiza” - Paguay Tenepaguay, Julia Fernanda (2024)
Student academic performance is a fundamental aspect that needs to be addressed both at the educational and health levels. In this context, it is essential to recognize that academic performance is linked to the appropriate nutritional status of students. Therefore, the evaluation of this relationship in educational institutions is of utmost importance and represents the research objectives: to understand the nutritional status and academic performance of students at “Dr. Edison Calle Loaiza” school in the city of Loja during the 2022-2023 academic period, identify sociodemographic characteristics, establish their nutritional status, determine academic performance, and establish the relationship between both variables. For this purpose, a quantitative relational-cross-sectional approach methodology was used. Anthropometric evaluation was applied, and nutritional status was classified using the Body Mass Index (BMI); academic performance was categorized according to standards set by the Ministry of Education and Culture of Ecuador. The obtained information was analyzed using the SPSS statistical tool. Finding that, out of the 118 students investigated, 52.5% (n=62) were male and 47.5% (n=56) were female; while 80.20% (n=84) were aged 8 to 11 years. Regarding nutritional status, 58.5% (n=69) showed normal weight, 26.3% (n=31) overweight, and 14.4% (n=17) were classified as obese. Concerning academic performance, 72% (n=85) achieved high academic performance, 26.3% (n=31) demonstrated medium performance, and 1.70% (n=2) showed low performance. Applying the chi-square statistical test with 6.56 degrees of freedom, a p-value of 6.56 was obtained, which is higher than the critical value (5.81) with a significance of 0.002. This study concludes the existence of a statistically significant relationship between student nutrition and academic performance